Porcine circovirus type 3 (PCV3) shedding in sow colostrum - Roongtham Kedkovid (2018)
© 2018 Elsevier B.V. The major objective of this work was to investigate the shedding of porcine circovirus type 3 (PCV3) in sow colostrum. PCV3 titers in the serum and colostrum samples of 38 sows were determined using qPCR. Interestingly, this is the first report regarding the identification of PCV3 from the colostrum samples. In the studied farm, the prevalence of PCV3 in the colostrum samples was 44.74% (17/38). When sows were grouped based on the PCV3 titers in the serum into the “High-viremic” “Low-viremic” and “Non-viremic” sows, it was shown that the High-viremic sows showed significantly higher PCV3 colostrum prevalence (100%; 9/9) with the PCV3 titers ranging from 4.01 to 7.33 genomic copies/mL. The results indicated that PCV3 in the colostrum might be partly influenced by the viremic stage of the infection. However, the results also showed that approximately 41% of sows shedding PCV3 with low titers in the colostrum (7/17) were non-viremic sows. In conclusion, this study identified the presence of PCV3 in sow colostrum. Clinical impacts and mechanisms of colostrum shedding of PCV3 should be further investigated.